HABITUASI SIKAP DAN PERILAKU POSITIF MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SDI BERTINGKAT PERUMNAS 3 KOTA KUPANG - Fransiska Andini; Petrus Ly; Treesly Y,N. Adoe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe and identify obstacles in the habituation of positive attitudes and behaviors through the Pancasila student profile strengthening project in Pancasila Education learning at SDI Bertingkat Perumnas 3 Kupang City. This study is a descriptive qualitative study. Data collection techniques used observation, interviews, and documentation. The subjects of the study were homeroom teacher and 17 students of grade 2 class A, homeroom teacher and 14 students of grade V class A, and the principal. The results of the study showed that the implementation of positive attitude and behavior habituation was carried out well and had positive results in accordance with the character values ​​contained in the Pancasila profile strengthening project. The attitudes and behaviors implemented include praying before and after learning, knowing and appreciating culture, collaboration, awareness of self-understanding and the situation faced, analyzing and evaluating reasoning, and producing original ideas. Obstacles in habituation are low self-management of students and limited collaboration between teachers and parents/guardians which results in the habituation process being hampered so that the goals of habituation have not been achieved optimally.